ANSWER
![f^(\prime)(x)=(√(x)(2x-9))/(2(x-3)^(3/2))](https://img.qammunity.org/2023/formulas/mathematics/college/w6w21z3nj6esnqy3eawnswg3cf4rpik11d.png)
Step-by-step explanation
Before finding the derivative of this function, we can simplify it. This will also simplify the process of derivation.
We include x inside the square root if we square it, and the same for the denominator (x - 3),
![f(x)=(x√(x(x-3)))/(x-3)=\sqrt{(x^2\cdot x(x-3))/((x-3)^2)}=\sqrt{(x^3)/(x-3)}](https://img.qammunity.org/2023/formulas/mathematics/college/j9vwxplcnm2n11g4ycazee5thz2a1h4y1b.png)
Now we apply the chain rule,
![h^(\prime)(g(x))=h^(\prime)(g)\cdot g^(\prime)(x)](https://img.qammunity.org/2023/formulas/mathematics/college/f3q1vth2f7i11vpl4fak35ij5e5gxxsv7m.png)
In this case, h(g) is the function f and g(x) is the expression inside the square root,
![f(g)=√(g);g(x)=(x^3)/(x-3)](https://img.qammunity.org/2023/formulas/mathematics/college/akx2r5c3j86z30tz05rw0fez1effvhagk6.png)
Let's find the derivative of f(g). Remember that the square root can be written as a power with exponent 1/2,
![f(g)=g^(1/2)\Rightarrow f^(\prime)(g)=(1)/(2)g^(1/2-1)=(1)/(2)g^(-1/2)=(1)/(2√(g))](https://img.qammunity.org/2023/formulas/mathematics/college/r39codr1zth5t9nh80l5lif3emloqcp6zj.png)
Then, find the derivative of g(x). To do so, we have to apply the quotient rule,
![\left((u(x))/(v(x))\right)^(\prime)=(u^(\prime)(x)\cdot v(x)-u(x)\cdot v^(\prime)(x))/(v^2(x))](https://img.qammunity.org/2023/formulas/mathematics/college/fnjhiwmvpx7kvmzvdkpssartmx9uxrmqyg.png)
In this case, u(x) = x³ and v(x) = x - 3. Let's find the derivative of each and the square of v(x),
![u^(\prime)(x)=3x^(3-1)=3x^2](https://img.qammunity.org/2023/formulas/mathematics/college/85ro8ovds9ha6z94yy59ea4nddmsaf5lgb.png)
![v^(\prime)(x)=x^(1-1)-0=1](https://img.qammunity.org/2023/formulas/mathematics/college/50vvk40a8ybhtkwg678jj8c5ds2z0d3hxt.png)
![v^2(x)=(x-3)^2](https://img.qammunity.org/2023/formulas/mathematics/college/t7qq1owrlrl0a57m51ty88s1jejk0bzq9e.png)
So, the derivative of g(x) is,
![g^(\prime)(x)=(3x^2(x-3)-x^3)/((x-3)^2)=(3x^3-9x^2-x^3)/((x-3)^2)=(2x^3-9x^2)/((x-3)^2)](https://img.qammunity.org/2023/formulas/mathematics/college/pu94kjmuxw727b3c88rhqev72dguuk0d8x.png)
Finally, plug in g'(x) and f'(g(x)) in the chain rule expression we found above,
![f^(\prime)(x)=\frac{1}{2\sqrt{(x^3)/(x-3)}}\cdot(2x^3-9x^2)/((x-3)^2)](https://img.qammunity.org/2023/formulas/mathematics/college/t3bui04ovnq526d5lo6lqgofdep374dfi1.png)
This expression can be simplified. First, distribute the square root of the first factor and rewrite it using fractional exponents,
![f^(\prime)(x)=((x-3)^(1/2))/(2x^(3/2))\cdot(2x^(3)-9x^(2))/((x-3)^(2))](https://img.qammunity.org/2023/formulas/mathematics/college/gyw889zq58z7fz2b6zawcxxpd87jpsr5dt.png)
Simplify the exponents of the factor (x - 3),
![f^(\prime)(x)=((x-3)^(1/2-2))/(2x^(3/2))\cdot2x^3-9x^2=((x-3)^(-3/2))/(2x^(3/2))\cdot2x^3-9x^2=(2x^3-9x^2)/(2x^(3/2)(x-3)^(3/2))](https://img.qammunity.org/2023/formulas/mathematics/college/1edocf9vv0ru7txm7uqcdsb7iv3dsfn3j7.png)
We can also take x² as a common factor in the numerator to simplify that with the denominator,
![f^(\prime)(x)=(x^2(2x^-9))/(2x^(3/2)(x-3)^(3/2))=(x^(2-3/2)(2x^-9))/(2(x-3)^(3/2))=(x^(1/2)(2x-9))/(2(x-3)^(3/2))](https://img.qammunity.org/2023/formulas/mathematics/college/gj25lnr0awvbw0m3js8yncg8siltz5medt.png)
Hence, the derivative of the function is,
![f^(\prime)(x)=(√(x)(2x-9))/(2(x-3)^(3/2))](https://img.qammunity.org/2023/formulas/mathematics/college/w6w21z3nj6esnqy3eawnswg3cf4rpik11d.png)